Study guides

☆☆

Q: -7x plus 9x -3

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Simplifying 2x + 3 = 9x Reorder the terms: 3 + 2x = 9x Solving 3 + 2x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 3 + 2x + -9x = 9x + -9x Combine like terms: 2x + -9x = -7x 3 + -7x = 9x + -9x Combine like terms: 9x + -9x = 0 3 + -7x = 0 Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Divide each side by '-7'. x = 0.4285714286 or x = 3/7 Simplifying x = 0.4285714286 or x = 3/7

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

2x+5=11 2x=6 x=3

7x = 4x - 93x = -9x = -3

2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x

Related questions

2x+3=9x 3=9x-2x 3=7x x=3/7

Simplifying 2x + 3 = 9x Reorder the terms: 3 + 2x = 9x Solving 3 + 2x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 3 + 2x + -9x = 9x + -9x Combine like terms: 2x + -9x = -7x 3 + -7x = 9x + -9x Combine like terms: 9x + -9x = 0 3 + -7x = 0 Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Divide each side by '-7'. x = 0.4285714286 or x = 3/7 Simplifying x = 0.4285714286 or x = 3/7

9x-8=7x-3 9x-7x=-3+8 2x=5 x=5/2 x=2.5

2x+3=9x-2x -2x3=7x/7 /73/7=x

2x+7x-10=4x+3-2x 9x-10=2x+3 7x=13 x=13/7ans

You can only add or subtract like terms. So, you subtract 9x from 2x, which gives you -7x. Then subtract -9 from 3 to get -6. And you are left with -7x -6.

2x+5=11 2x=6 x=3

7x = 4x - 93x = -9x = -3

2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x

5 + 7x + 2x - 3 + 6Collect the 'x'-terms: 7x + 2x = 9xCollect all the number terms: 5 - 3 + 6 = 8So the original expression, after it's cleaned up, is the same as ( 9x + 8 ).

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

21x2 + 27x - 30 = 3*(7x2 + 9x - 10) = 3*(7x2 - 5x + 14x - 10) =3*[x*(7x - 5) + 2*(7x - 5)] = 3*(7x - 5)*(x + 2)

People also asked

Featured Questions